2022
DOI: 10.1128/spectrum.00666-22
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of SpoVAEa Protein Dynamics in Dormant Spores of Bacillus cereus and Dynamic Changes in Their Germinosomes and SpoVAEa during Germination

Abstract: Bacillus cereus is commonly present in soil and infects humans via contaminated food. In this study, we used B. cereus spores to investigate the movement of the spore-specific inner membrane (IM) channel protein SpoVAEa, the interaction between SpoVAEa and the germinosome scaffold protein GerD, and the dynamics of germinosomes with GerR and GerD in spore germination.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…It would appear that DPA is the master component whose movement determines the sporulation or germination of a vegetative cell. Indeed, in a recent study using B. subtilis, it was suggested that the subunits of the SpoVa proteins that form channels and cytoplasmic plugs play a role in the efficiency of DPA import (sporulation) and export (germination) [37,38,135]. DPA transport into the spores involves cycles of unplugging and then replugging the C-Eb membrane channel.…”
Section: The General Spore Germination Program In the Genus Bacillusmentioning
confidence: 99%
See 4 more Smart Citations
“…It would appear that DPA is the master component whose movement determines the sporulation or germination of a vegetative cell. Indeed, in a recent study using B. subtilis, it was suggested that the subunits of the SpoVa proteins that form channels and cytoplasmic plugs play a role in the efficiency of DPA import (sporulation) and export (germination) [37,38,135]. DPA transport into the spores involves cycles of unplugging and then replugging the C-Eb membrane channel.…”
Section: The General Spore Germination Program In the Genus Bacillusmentioning
confidence: 99%
“…DPA transport into the spores involves cycles of unplugging and then replugging the C-Eb membrane channel. Nutrient detection during germination triggers DPA release by unplugging the C-Eb [37,38,135] (Figure 3).…”
Section: The General Spore Germination Program In the Genus Bacillusmentioning
confidence: 99%
See 3 more Smart Citations